Thermal behavior of alginic acid and its sodium salt - Soares, João da Paixão; dos Santos, Jose Estrela; Chierice, Gilberto Orivaldo; Cavalheiro, Éder Tadeu Gomes (Eclética Química, 2004)
An evaluation of hydration and thermal decomposition of HAlg and its sodium salt is described using thermogravimetry (TG) and differential scanning calorimetry (DSC). TG curves in N 2 and air, were obtained for alginic acid showed two decomposition steps attributed to loss of water and polymer decomposition respectively. The sodium alginate decomposed in three steps. The first attributed to water loss, followed by the formation of a carbonaceous residue and finally the Na 2 CO 3 . DSC curves presented peaks in agreement with the TG data. In the IR alginic acid presented bands at 1730 and 1631 cm -1 , while sodium alginate presented a doublet at 1614 e 1431 cm -1 , evidencing the presence of salified carboxyl groups.